2022
DOI: 10.3390/ijerph191710604
|View full text |Cite
|
Sign up to set email alerts
|

California WIC Participants Report Favorable Impacts of the COVID-Related Increase to the WIC Cash Value Benefit

Abstract: The United States Department of Agriculture approved an increase to the Cash Value Benefit (CVB) for the purchase of fruits and vegetables issued to participants receiving an eligible Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) food package. In order to understand satisfaction, perceptions, and the overall impact of additional benefits for fruits and vegetables at the household level, a qualitative study consisting of structured phone interviews was conducted with families ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Duffy et al (2022) [ 74 ] explored awareness, barriers and facilitators, and perceived impact of the higher allotment for FVs among WIC participants in North Carolina. Martinez et al (2022) [ 75 ] explored satisfaction and use of the higher FV allotment among WIC participants in southern California. Results from both studies indicated WIC participants believed the prior allotment for FVs was too low to support accessing adequate variety and quality of FVs [ 74 , 75 ].…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Duffy et al (2022) [ 74 ] explored awareness, barriers and facilitators, and perceived impact of the higher allotment for FVs among WIC participants in North Carolina. Martinez et al (2022) [ 75 ] explored satisfaction and use of the higher FV allotment among WIC participants in southern California. Results from both studies indicated WIC participants believed the prior allotment for FVs was too low to support accessing adequate variety and quality of FVs [ 74 , 75 ].…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
“…Martinez et al (2022) [ 75 ] explored satisfaction and use of the higher FV allotment among WIC participants in southern California. Results from both studies indicated WIC participants believed the prior allotment for FVs was too low to support accessing adequate variety and quality of FVs [ 74 , 75 ]. Martinez and colleagues also find evidence that the increased FV allotment not only favorability impacted WIC participants, but also improved FV accessibility/consumption for other household members [ 75 ].…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies in California [ 25 , 26 ], North Carolina [ 27 ], and Delaware [ 28 ] suggest that this temporary increase is highly valued by WIC caregivers and may be linked with improvements in FV affordability, purchasing, and consumption, as well as overall WIC satisfaction. However, research on the perceived impact of this emergent temporary increase remains limited to mostly qualitative studies [ 25 , 27 , 28 ]. It is also unclear whether any potential benefits or impacts of the CVB increase may have been mitigated by structural inequities in access to FV.…”
Section: Introductionmentioning
confidence: 99%